Um novo enfoque teórico para os convênios com entidades privadas - Roberto, Luiz Fernando (2013)
This paper aims to describe the normative framework that regulates agreements with private entities and their recent movements. From the construction of a critical view on the matter, the estudy discusses the core ideas that base traditional forms of selection of the private partner and the restrictions to internal management of entities. Pointing lack of objectivity and excessive cost in the existing system, the paper proposes a new theoretical approach to the matter, in which planning and administrative simplification can be used as tools for a more effective control over public resources transferred by the Estate